Biodiesel feedstock determines exhaust toxicity in 20% biodiesel: 80% mineral diesel blends. (January 2023) - Landwehr, Katherine R.; Hillas, Jessica; Mead-Hunter, Ryan; King, Andrew; O'Leary, Rebecca A.; Kicic, Anthony; Mullins, Benjamin J.; Larcombe, Alexander N.; ,
Abstract: To address climate change concerns, and reduce the carbon footprint caused by fossil fuel use, it is likely that blend ratios of renewable biodiesel with commercial mineral diesel fuel will steadily increase, resulting in biodiesel use becoming more widespread. Exhaust toxicity of unblended biodiesels changes depending on feedstock type, however the effect of feedstock on blended fuels is less well known. The aim of this study was to assess the impact of biodiesel feedstock on exhaust toxicity of 20% blended biodiesel fuels (B20). Primary human airway epithelial cells were exposed to exhaust diluted 1/15 with air from an engine running on conventional ultra-low sulfur diesel (ULSD) or 20% blends of soy, canola, waste cooking oil (WCO), tallow, palm or cottonseed biodiesel in diesel. Physico-chemical exhaust properties were compared between fuels and the post-exposure effect of exhaust on cellular viability and media release was assessed 24 h later. Exhaust properties changed significantly between all fuels with cottonseed B20 being the most different to both ULSD and its respective unblended biodiesel. Exposure to palm B20 resulted in significantly decreased cellular viability (96.3 ± 1.7%; p < 0.01) whereas exposure to soy B20 generated the greatest number of changes in mediator release (including IL-6, IL-8 and TNF-α, p < 0.05) when compared to air exposed controls, with palm B20 and tallow B20 closely following. In contrast, canola B20 and WCO B20 were the least toxic with only mediators G-CSF and TNF-α being significantly increased. Therefore, exposure to palm B20, soy B20 and tallow B20 were found to be the most toxic and exposure to canola B20 and WCO B20 the least. The top three most toxic and the bottom three least toxic B20 fuels are consistent with their unblended counterparts, suggesting that feedstock type greatly impacts exhaust toxicity, even when biodiesel only comprises 20% of the fuel. Graphical abstract: Image 1 Highlights: Exhaust characteristics changed significantly between different feedstock types. Cottonseed biodiesel blend exhaust was the most different to commercial diesel. Biodiesel feedstock type altered exhaust toxicity when making up 20% of the fuel. Canola biodiesel was the least toxic type tested and Palm and Soy were the most.